Adsorption of bacteria to roots as related to host specificity in the Rhizobium-clover symbiosis. - Dazzo, F B (1976)
Quantitative microscope techniques were utilized to examine the adsorption of rhizobial cells to clover root hairs. Adsorption of cells of noninfective strains of Rhizobium trifolii or infective R. meliloti strains to clover root hairs was four to five times less than that of the infective R. trifolii strains. Attachment of the rod-shaped bacteria to clover root cells occurred in a polar, end-on fashion. Viable or heat-killed R. trifolii cells precoated with a clover lectin having 2-deoxyglucose specificity had increased adsorption to clover roots. Adsorption of bacteria to roots was not increased if the clover lectin was inactivated by heat or 2-deoxyglucose treatment prior to incubation with R. trifolii. Adsorption of R. trifolii to clover root hairs was inhibited by 2-deoxyglucose (30 mM) but not by 2-deoxygalactose or alpha-D-glucose. Adsorption of R. meliloti cells to alfalfa root hairs was not affected by 2-deoxyglucose at that concentration. These results suggest that expression of host specificity in the Rhizobium-clover symbiosis involves a preferential adsorption of infective cells to clover root hairs through a 2-deoxyglucose-sensitive receptor site.